Ganoderma tsugae Induces S Phase Arrest and Apoptosis in Doxorubicin-Resistant Lung Adenocarcinoma H23/0.3 Cells via Modulation of the PI3K/Akt Signaling Pathway. (26th June 2012) - Yu, Yang-Hao; Kuo, Han-Peng; Hsieh, Hui-Hsia; Li, Jhy-Wei; Hsu, Wu-Huei; Chen, Shih-Jung; Su, Muh-Hwan; Liu, Shwu-Huey; Cheng, Yung-Chi; Chen, Chih-Yi; Kao, Ming-Ching
Abstract : Ganoderma tsugae (GT) is a traditional Chinese medicine that exhibits significant antitumor activities against many types of cancer. This study investigated the molecular mechanism by which GT suppresses the growth of doxorubicin-resistant lung adenocarcinoma H23/0.3 cells. Our results reveal that GT inhibits the viability of H23/0.3 cells in vitro and in vivo and sensitizes the growth suppression effect of doxorubicin on H23/0.3 cells. The data also show that GT induces S phase arrest by interfering with the protein expression of cyclin A, cyclin E, CDK2, and CDC25A. Furthermore, GT induces cellular apoptosis via induction of a mitochondria/caspase pathway. In addition, we also demonstrate that the suppression of cell proliferation by GT is through down-regulation of the PI3K/Akt signaling pathway. In conclusion, this study suggests that GT may be a useful adjuvant therapeutic agent in the treatment of lung cancer.